Development of Student Worksheets Based on Engineering Design Process to Enhancing Student’s Scientific Literacy in Middle School Students - Kasah, Iwang Jouvanda; Putra, Pramudya Dwi Aristya; Rusdianto, Rusdianto (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
Scientific literacy is the ability to actively participate in discussions and understanding issues related to science and scientific ideas, serving as a form of participation as an informed citizen. The objective of this research is to examine the validity, practicality, and effectiveness of a student worksheets based on the engineering design process (EDP). The research type and design fall under research and development (R&D) and have been developed using the ADDIE research design through the steps of Analyze, Design, Develop, Implement, and Evaluate. Data collection included validation and student response questionnaires, implementation sheets, and scientific literacy tests to assess validity, practicality, and effectiveness. The validation questionnaire is used to measure validity, the student response questionnaire is used to determine student responses, the implementation sheet is used to assess the feasibility of the learning process, and the science literacy test is used to assess the improvement in students' scientific literacy. The validity analysis yielded a result of 90%, categorizing the EDP-based student worksheets as very valid. The practicality score of 86% demonstrates that the worksheets are highly practical for use in learning environments. Additionally, the effectiveness, measured through an N-gain value of 0.76, indicates a significant improvement in students’ scientific literacy. The student response questionnaire results, with an 84% score, reflect a very positive reception from students. These findings collectively confirm that the EDP-based student worksheets are valid, practical, and effective tools for enhancing scientific literacy among junior high school students. These results suggest that EDP-based worksheets can be a valuable tool for fostering scientific literacy among junior high school students, equipping them with the skills to engage in scientific discussions and make informed decisions as active citizens.